Fabrication of Pneumatic Series Coupler for Belt Conveyor - Prakash Kajale, Darshan; Bhadane, Kalpesh; Joshi, Dinesh; Kale, Akash; Patil, Tushar (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
A conveyor system is a common piece of mechanical handling equipment that moves materials from one location to another. Conveyor systems are commonly used in many industries, including the automotive, agricultural, computer, electronic, food processing, aerospace, pharmaceutical, chemical, bottling and canning, print finishing and packaging. Although a wide variety of materials can be conveyed, some of the most common include food items such as beans and nuts, bottles and cans, automotive components, scrap metal, pills and powders, wood and furniture and grain and animal feed. Many factors are important in the accurate selection of a conveyor system. It is important to know how the conveyor system will be used beforehand. Some individual areas that are helpful to consider are the required conveyor operations, such as transportation, accumulation and sorting, the material sizes, weights and shapes and where the loading and pickup points to need. The applications of belt conveyer while loading in goods carrier trucks or trailers wagon there is limitations of conveyer length & positions. Because the conveyer only transport the materials up to first corner of the goods carrier trucks & next steps to manual material handling inside the truck, so that to overcome this problem we can develop the split belt conveyer in which half part of conveyer is outside the goods carrier trucks & half part of conveyer is inside the truck. The objectives of this concepts to minimize material handling time, effort & cost in the packaging & transportation system industries.
Keywords: double acting cylinder; dc motor; pneumatic fittings; safety rollers